Tinjauan Undang-Undang ITE Jo. Undang-Undang Tindak Pidana Mentransmisikan Informasi Elektronik yang Bermuatan Seksual Melalui Media Sosial di Polres Wajo - Muharawati; Andi Dadi Mashuri; Kemala Husada; Andi Muh Nabil BZ; Siti Hardiananti (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2026)
This study aims to determine the application of the ITE Law in conjunction with Law Number 19 of 2016 in handling the crime of transmitting electronic information containing sexual content through social media at the Wajo Police Station; and to determine the factors that influence the application of the ITE Law in conjunction with Law Number 19 of 2016 in handling the crime of transmitting electronic information containing sexual content through social media at the Wajo Police Station. The data collection method used was interviews and library research. The data were analyzed qualitatively using deductive and inductive methods and then presented descriptively. The results of the study indicate that the application of the ITE Law in conjunction with Law Number 19 of 2016 in handling the crime of transmitting electronic information shows that it has been carried out procedurally and normatively, but is still faced with various substantive, structural, and cultural challenges; and the factors that influence the application of the ITE Law in conjunction with Law Number 19 of 2016. Law Number 19 of 2016 in handling the crime of transmitting sexually charged electronic information through social media at the Wajo Police Resort is influenced by factors such as legal substance, legal structure, legal culture, technical factors in proving ITE crimes, victim and perpetrator factors, and policy and law enforcement discretion.